A Hierarchical Modeling Framework for Cyber-Physical Micro Energy Grid System - Yang, Yi; Lu, Guanpeng; Li, Zhuangzhuang; Tang, Yufeng (Frontiers in Energy Research, 2021)
This paper proposes a hierarchical modeling framework for micro energy grid (MEG) from the perspective of cyber-physical integration, including three layers: object layer, integration layer and decision layer. This modeling framework can fully reveal the interplay of the information flow and energy flow in MEG. The energy hub approach is used to uniformly describe the conversion and distribution of different energy sources in the object layer. The state machine is used to describe the characteristics of energy flow and information flow and their dynamic relationships in the integration layer, where the energy flow describes the dynamic balance of energy between the supply side and demand side and the energy changes of each unit in MEG, and the information flow describes the transferring process of each unit's operating state and the conditions triggering the state transformation. The optimization objective of the decision layer is established based on the actual requirements with optimal operation. The combination of the three-layer model forms the overall model of the MEG. Finally, a typical MEG system is taken as an example to verify the proposed modeling approach, and the results show that the proposed modeling method effectively improves the observability and optimal operation of the MEG.